New and Old in «Caritas in Veritate» - Sanz de Diego, Rafael (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
The recent Encyclical of the Pope (Caritas in Veritate) brings together a good part of the previous Social Doctrine, especially Populorum Progessio, which it commemorates, twenty years after its publication, and other documents, too: Quadragesimo Anno which was published two years after the crisis of 1929 and several magisterial interventions of Joseph Ratzinger before and after he became Pope. Logically, it also contributes some novelties, due in part to the circumstances in which it comes out, as well as to the personal characteristics of Benedict XVI.
Keywords: Caritas in Veritate; Ratzinger; Pope Benedict XVI; Church’s Social Doctrine